An empirical approach to modeling ion production rates in Titan's ionosphere I: Ion production rates on the dayside and globally. Issue 2 (3rd February 2015) - Richard, M. S.; Cravens, T. E.; Wylie, C.; Webb, D.; Chediak, Q.; Perryman, R.; Mandt, K.; Westlake, J.; Waite, J. H.; Robertson, I.; Magee, B. A.; Edberg, N. J. T.
Abstract Titan's ionosphere is created when solar photons, energetic magnetospheric electrons or ions, and cosmic rays ionize the neutral atmosphere. Electron densities generated by current theoretical models are much larger than densities measured by instruments on board the Cassini orbiter. This model density overabundance must result either from overproduction or from insufficient loss of ions. This is the first of two papers that examines ion production rates in Titan's ionosphere, for the dayside and nightside ionosphere, respectively. The first (current) paper focuses on dayside ion production rates which are computed using solar ionization sources (photoionization and electron impact ionization by photoelectrons) between 1000 and 1400 km. In addition to theoretical ion production rates, empirical ion production rates are derived from CH4, CH3+, and CH4+ densities measured by the INMS (Ion Neutral Mass Spectrometer) for many Titan passes. The modeled and empirical production rate profiles from measured densities of N2+ and CH4+ are found to be in good agreement (to within 20%) for solar zenith angles between 15 and 90°. This suggests that the overabundance of electrons in theoretical models of Titan's dayside ionosphere is not due to overproduction but to insufficient ion losses.